PTH 1-34 (teriparatide) may not improve healing in proximal humerus fractures: A randomized, controlled study of 40 patients. (2nd January 2016) - Johansson, Torsten
Abstract : Background and purpose — There is solid evidence from animal experiments that parathyroid hormone (PTH) improves fracture healing. So far, only 3 papers on PTH and fracture repair in humans have been published. They suggest that PTH may enhance fracture healing, but the results do not appear to justify specific clinical recommendations. This study was carried out to determine whether teriparatide enhances fracture healing of proximal humerus fractures. Patients and methods — 40 post-menopausal women with a proximal humerus fracture were randomized to either daily injections with 20 µg teriparatide (PTH 1-34 (Forteo)) for 4 weeks or control treatment. At randomization, the patients were asked to assess how their pain at rest and during activity (visual analog scale (VAS)) and also function (DASH score) had been prior to the fracture. At 7 weeks and again at 3 months, their current state was assessed and the tests were repeated, including radiographs. 2 radiologists performed a blind qualitative scoring of the callus at 7 weeks. Callus formation was arbitrarily classified as "normal" or "better". Results — 39 patients completed the follow-up. The radiographic assessment showed a correct correlation, "better" in the teriparatide group and "normal" in the control group, in 21 of the 39 cases. There were no statistically significant differences in pain, in use of strong analgesics, or in function between the groups at the follow-up examinations. Interpretation — There were no radiographic signs of enhanced healing or improved clinical results in the group treated with teriparatide